ANALYSIS OF OXIDATIVE STRESS MARKERS IN CHRONIC CONSUMPTION OF MONOSODIUM GLUTAMATE ON LIVER OF WISTAR ALBINO RATS - BABU THANGACHI, SURENDRA; MOKHASI, VARSHA SRIRAM; MURTHUZA, AGA AMMAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study was intended to explore whether Monosodium glutamate (MSG) induces oxidative stress on the liver of Wistar albino rats when fed chronically at three different doses, namely, low, mid, and high doses identical to human consumption doses in growing countries. Methods: The acclimatized Wistar albino rats (n=24) were randomly selected and grouped into four groups, namely Control, Low dose MSG (180 mg kg), Mid dose MSG (360 mg/kg), and High dose MSG (720 mg/kg). The animals were orally administered MSG for 120 days. After completion of the experimental period (120 days), euthanized animal liver was homogenized to investigate the oxidative stress marker enzymes such as Superoxide Dismutase (SOD), Glutathione Peroxidase (GPx), Catalase (CAT), and Myeloperoxidase (MPO). Results: The MPO showed a significant increase (p<0.05) in liver homogenate of all MSG induced groups when compared to control group. The SOD, CAT, and GPx activity deteriorated (p<0.05) in monosodium induced groups contrasting to the control group. Conclusion: The effects of MSG on oxidative stress markers on liver homogenate in the current study exhibited erratic abnormal changes in oxidative stress markers of monosodium induced groups which contemplate the harmful effects of MSG consumed chronically. The further studies should confirm the genetic basis of oxidative stress damage and transform the safety regulations of MSG consumption throughout the world.